If the sum of the first `2n`terms of the A.P. 2, 5, 8, …, is equal to the sum of the first `n`terms of A.P. 57, 59, 61, …, then `n`equals

A. 10

B. 12

C. 11

D. 13

A. 10

B. 12

C. 11

D. 13

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Please briefly explain why you feel this question should be reported.

Please briefly explain why you feel this answer should be reported.

Please briefly explain why you feel this user should be reported.

Correct Answer – C

We have,

`(2n)/(2){2xx2+(2n-1)xx3}=(n)/(2){2xx57+(n-1)xx2}`

`rArr” “n(6n+1)=n(n+56)`

`rArr” “5n^(2)-55n=0rArrn=11” “[becausen!=0]`